'Be prepared and give it a go!' Transitions into further education for learners with additional learning needs. (6th May 2022) - Packer, Rhiannon; Abbinett, Emily; Morris, Emily
Abstract : Transitions in education are known to have an impact on learners both in social and emotional terms as well as academically. This article argues that transition experiences should be regarded as an on‐going process rather than a one‐off event. The move from compulsory education at the age of 16 can have a significant impact on engagement and retention, particularly for learners with additional learning needs (ALN), yet this is an underexplored area. While the transition from compulsory education to a further education (FE) setting brings increased independence, new opportunities and the emergence of adulthood, it can also be a time of trepidation and uncertainty for all learners, including those with ALN. Using an interpretive methodology, the voices of key stakeholders in the transition to FE from one setting were recorded to explore and inform good practice. Data were gathered using online questionnaires, interviews and focus groups. Findings ascertained the value of nurturing effective practitioner–learner relationships in preparation for transition, the importance of developing peer support networks and the provision of a central, safe space that is accessible to learners with ALN at all times.